INVESTMENT IN UKRAINE: MAIN TENDENCIES, PROBLEMS AND PROSPECTS OF ACTIVATION - LOZA Svіtlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Investment is the primary catalyst for the development of any country. Without appropriate investment, recovery and a prosperous future for Ukraine are impossible. Despite thorough studies of domestic and foreign investment trends, more attention should be paid to analyzing the impact of crisis phenomena on the dynamics and structure of investments. The search for the main directions of activation of investment processes in conditions of the acute need for financial resources for the recovery of Ukraine requires further elaboration. The article aims to study the main trends, risks, and prospects for activating investment processes in Ukraine. The article analyzed the dynamics and studied the most important factors influencing the leading socio-economic indicators of Ukraine for 1997-2020. The level of investment intensity in the economy of Ukraine for 1995-2020 was evaluated, which showed that only within five years ( 2004-2008) the intensity of investments exceeded the bar of 20%. Ukraine never recovered after the global financial crisis of 2008-2009. Peculiarities of the influence of unpredictable factors and crisis phenomena on the volume and structure of investment attraction from various sources of financing have been studied. A study of the dynamics of foreign direct investments for 1995-2020 was conducted. The main directions and prerequisites for the activation of investments in the economy of the country, which is actually in a state of war, as well as its post-war recovery, were outlined. It was established that for the full-scale attraction of investments from investment funds, private investors, and grant funds, the availability of available and reliable information about promising investment projects and possible benefits from their implementation is of utmost importance; practical tools of public administration; a transparent system of project verification and an effective system of monitoring their results with the possibility of information exchange; minimization of corruption risks; working out the mechanism of insurance of investment risks during the war.